Risk, Focus of Loss and Minimum Income in Rainfed Lowland Rice Farming - Sri Mardiyati; Mohammad Natsir (Cita konsultindo, 2026)
This study aims to analyze the levels of production risk, cost risk, and revenue risk, as well as the tolerable risk of loss (focus of loss) and minimum income of rain-fed lowland rice farming in the Tanakeke Islands District, Takalar Regency. Primary data collection methods used direct interviews (questionnaires) and field observations. A sample of 82 farmers was selected for this study. Data analysis used descriptive analysis and the Coefficient of Variation (CV). The results indicate that the highest risk of loss borne by rain-fed lowland rice farmers is cost risk, at 23.65 percent. Production risk, meanwhile, reached 13.74 percent and revenue risk, at 14.6 percent. Rain-fed lowland rice farming income is generated only in one planting season per year, averaging Rp 23,803,482.62 per hectare, with total farming costs of Rp 5,201,110.34 per hectare. The average household expenditure of rice farmers reaches Rp 16,423,225.61 per year. The minimum income earned by rain-fed rice farmers to continue farming and meet household needs is Rp 21,624,335.95 per year, with a tolerable or reasonable risk of loss accepted by rice farmers of Rp 2,179,146.67 per hectare. The focus of loss value or risk of loss that can be accepted by rice farmers is 9.15 percent, meaning that if the risk of loss occurs above this value, farmers will experience financial constraints in continuing farming and meeting their household needs.